2016
DOI: 10.1530/rep-16-0188
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenin2: spermatozoon specificity and immunoprotection in mud crabs

Abstract: As the precursor of vitellin (Vn), vitellogenin (Vg) has initially been considered as a female-specific protein involved in vitellogenesis, while it was also present in males induced by hormones or organs manipulation. Distinct from vtg1 we previously found in female mud crab Scylla paramamosain, vtg2 was intriguingly detected in male testis under normal physiological conditions in this study. Sequence analysis showed that vtg2 and vtg1 were actually two isoforms of Vg caused by different types of alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…The mud crab, S. paramamosain, is an annual animal and reproduces once in its lifetime. The ovarian development goes through three main stages: pre-vitellogenic stage, earlyvitellogenic stage, and late-vitellogenic stage (30,31). In this study, Sp-CFSH expression was also found to be different in females during ovarian development.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The mud crab, S. paramamosain, is an annual animal and reproduces once in its lifetime. The ovarian development goes through three main stages: pre-vitellogenic stage, earlyvitellogenic stage, and late-vitellogenic stage (30,31). In this study, Sp-CFSH expression was also found to be different in females during ovarian development.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, the eyestalk ganglion of female crabs (n = 8) were collected to analyze the Sp-CFSH expression. Ovarian development was distinguished according to the morphological characteristics and confirmed by histological observation (30,31). All the animals used in this study have been approved by the Animal Ethics Committee of Xiamen University.…”
Section: Animal Sourcesmentioning
confidence: 99%
“…may have an antimicrobial function or immune-related functions (18)(19)(20)(21). For example, in the crab, a Vg2 cDNA was detected in the hemocyte and the function of the Vg2 appeared to be immunity-related (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Vg can protect some species from oxidative stress, such as the honey bee, nematodes ( Caenorhabditis elegans ), and fish ( Anguilla japonica ) (Ando and Yanagida, 1999; Nakamura et al, 1999; Seehuus et al, 2006). In addition, Vg plays important roles during immunity in amphioxus (Zhang et al, 2005), fish (Li et al, 2008, 2009; Liu et al, 2009; Garcia et al, 2010), bay scallop (Wu et al, 2015), mud crab (Yang et al, 2016), and noble scallop (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%